Gift-exchange Game Theory for Gamification on Digital Data Collection Systems - Supriyanto, Supriyanto; Fahana, Jefree (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol 11 No 1 (2020): Vol. 11, No. 1 April 2020, 2020)
Gamification is widely used to increase user motivation by applying game elements to things that are not game-based. For example, in a data collection system. Gamification is used to increase the motivation of users to want to get involved. The elements of the game that are often used are rewards, badges, and leaderboards. But some implementations have not been able to ensure increased user motivation. Gamification applied needs to consider the use of game theory. Game theory is used to determine the right gamification model for digital data collection. This paper discusses the application of gift-exchange-games (GEG) in the gamification of digital data collection systems. GEG is used to model player interactions in the gamification system. GEG implementation of Gamification can improve user involvement in the system. This theoretical model can later be used for a more efficient data collection system development platform . Keywords : gamification, game theory, data collection, gift-exchange-game, geg